Reductions in soil water nitrate beneath a perennial grain crop compared to an annual crop rotation on sandy soil - Reilly, Evelyn C.; Gutknecht, Jessica L.; Sheaffer, Craig C.; Jungers, Jacob M. (Frontiers in Sustainable Food Systems, 2022)
Nitrate (NO3--N) leaching into groundwater as a result of high nitrogen (N) fertilizer rates to annual crops presents human health risks and high costs associated with water treatment. Leaching is a particularly serious concern on sandy soils overlying porous bedrock. Intermediate wheatgrass (IWG) [Thinopyrum intermedium (Host.) Barkw. & D.R. Dewey], is a perennial grass that is being bred to produce agronomically and economically viable grain, which is commercially available as Kernza®. Intermediate wheatgrass is a low-input crop has the potential to produce profitable grain and biomass yields while reducing NO3--N leaching on sandy soils compared with common annual row crop rotations in the Upper Midwest. We compared grain yields, biomass yields, soil solution NO3--N concentration, soil extractable NO3--N, soil water content, and root biomass under IWG and a conventionally managed corn (Zea mays L.) and soybean [Glycine max (L.) Merr.] rotation for 3 years on a Verndale sandy loam in Central Minnesota. Mean soil solution NO3--N was 77–96% lower under IWG than the annual crop rotation. Soil water content was greater under annuals compared to IWG early in the growing season, suggesting greater water use by IWG during this time. Interactions between crop treatments and depth were observed for soil water content in Year 3. Root biomass from 0 to 60 cm below the soil surface was five times greater beneath IWG compared to soybean, which may explain differences in soil extractable and solution NO3--N among crops. With irrigation on coarse structured soils, IWG grain yields were 854, 434, and 222 kg ha−1 for Years 1–3 and vegetative biomass averaged 4.65 Mg ha−1 yr−1; comparable to other reports on heavier soils in the region. Annual crop grain yields were consistent with local averages. These results confirm that IWG effectively reduces soil solution NO3--N concentrations even on sandy soils, supporting its potential for broader adoption on land vulnerable to NO3--N leaching.